Influence of the Process Parameters on the Microhardness and the Wear Resistance of Friction Stir Processed H65 Copper Alloy - Igor Kolupaev; Xiaole Ge; Weiwei Song; Di Jiang; Jiafei Pu; Hongfeng Wang; Yuan Chu (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
Friction stir processing (FSP) was used to modify a larger-size surface of H65 copper alloy. The influence of the traverse speed and the rotation speed on the microstructure, the microhardness and the wear resistance of the modified surface were analyzed. The wear mechanism of the modified H65 copper alloy was revealed. The results indicate that the grain size was greatly refined after FSP compared with the parent metal and that the grain size increased with the increment of the rotation speed. The average microhardness of the modified surface was higher than that of the parent metal. The average microhardness had a highest value of 174.13 HV when the traverse speed was 200 mm/min and the rotation speed was 200 rpm, i.e., 21% higher than that of the parent metal. The average microhardness decreased with the increase of the rotation speed. When the traverse speed was 200 mm/min and the rotation speed was 600 rpm, the average friction coefficient of the modified surface was the smallest (0.3213), which was lower than that of the parent metal (0.3810). The wear mechanism of the H65 copper alloy modified by FSP was mainly adhesive wear accompanied by local abrasive wear.